Socio Juridical Analysis of Underage Marriage Caused by Pre-Marital Pregnancy: a Case Study in Banggai Islands Regency - Wardin Tolodo; Muhammad Akbar; M. Taufan B. (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2022)
This study discusses a socio-juridical analysis of underage marriages caused by pre-marital pregnancy in Banggai Islands Regency. The aims of this study are to discuss socio-juridical review of underage marriage in Banggai Islands Regency and the impacts from the existence of underage marriages on household harmony. This study used a qualitative method. The data was collected through direct observation, in-depth interviews, and writeen document analysis. The data, then, was analysed using themnatic analysis to find themes from the data. This study found that based on Law no. 16 of 2019 concerning marriage age limit, women are permitted to be married after age nineteen years old and . However, in an eergency case, a woman under nineteen years olad is allowed to be marreid if her parents obtain a dispensation from the religious court. Such emergency condition may be pre-marital pregnancy or economic problems. In some cases of underage marriage, we found that cauples underage marriages experience more negative impacts than positive impacts on the harmony in the their relationship. Negative impacts include women physical and mental health, and also economic limitation. We also found that most of pre-marital pregnancies were caused by permissive relationship, low education, lack of parental attention, promiscuity, misuse of technology, and lack of knowledge or understanding of religion.